1999
DOI: 10.1016/s0891-5520(05)70040-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Vaccines

Abstract: In a few short years, genetic vaccine technology has moved rapidly from a novel concept to an important strategy for the development of human and veterinary vaccines, for numerous indications. This article discusses current areas in which further refinements in technology will influence a variety of infectious disease treatments, including intramuscular and intradermal inoculation, gene gun inoculation, the mechanism of antigen presentation, and the use of genetic adjuvants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 109 publications
1
10
0
Order By: Relevance
“…CpG motifs exert their immunostimulatory potential by a pathway involving receptor-mediated endocytosis of CpG-containing DNA into immune cells (macrophages, DC, and B cells) followed by endosome acidification and likely degradation of the DNA into CpG-containing oligonucleotides (1). Particle-mediated ("gene gun") DNA vaccines bypass this signaling mechanism because of the direct intranuclear and intracytoplasmic deposition of intact plasmid DNA (23). This is evidenced by the fact that particle-mediated and needleinoculated DNA vaccines induce qualitatively different responses that are dependent on the method rather than the location of vaccine administration (17,35).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CpG motifs exert their immunostimulatory potential by a pathway involving receptor-mediated endocytosis of CpG-containing DNA into immune cells (macrophages, DC, and B cells) followed by endosome acidification and likely degradation of the DNA into CpG-containing oligonucleotides (1). Particle-mediated ("gene gun") DNA vaccines bypass this signaling mechanism because of the direct intranuclear and intracytoplasmic deposition of intact plasmid DNA (23). This is evidenced by the fact that particle-mediated and needleinoculated DNA vaccines induce qualitatively different responses that are dependent on the method rather than the location of vaccine administration (17,35).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to improved delivery, any DNA vaccine, with or without a specific delivery system, can potentially benefit from the inclusion of an adjuvant to augment the strength or quality of a given response. To this end, several investigators have demonstrated the ability to modulate the responses to both naked DNA and particle-based DNA vaccines by inclusion of vectors encoding a variety of cytokines and chemokines (23,24,36,40,46).Our efforts to identify a safe and potent adjuvant for particle-mediated DNA vaccines have recently focused on cholera toxin (CT) and the related Escherichia coli heat-labile enterotoxin (LT). CT and LT are two of the most powerful adjuvants known, due to their ability to elicit robust mucosal and systemic responses via the mucosal and parenteral routes (37, 50).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…There has also been considerable recent interest in development of novel, nucleic acid-based DNA vaccines for prevention of herpesvirus infections (29). These vaccines are simple to produce and administer, and induce both humoral and cell-mediated immune responses (19). HCMV gB and UL83 DNA vaccines induce antibody responses in mice (12,21,24), but there is little information about CMV DNA vaccine responses in relevant, species-specific models, and there have been no previous reports of GPCMV DNA vaccines.…”
Section: Introductionmentioning
confidence: 99%